AlGaN multiple quantum well deep‐ultraviolet micro‐light‐emitting diodes for high color conversion efficiency quantum dots display. Issue 7 (13th February 2022) - Feng, Feng; Liu, Yibo; Zhang, Ke; Lin, Yonghong; Chan, Ka‐Wah; Kwok, Hoi‐Sing; Liu, Zhaojun
Abstract: Displays based on inorganic micro‐light‐emitting diodes (micro‐LEDs) are highly anticipated for next‐generation technologies. AlGaN‐based deep‐ultraviolet (deep‐UV) micro‐LED as the excitation source for quantum dots display with high efficiency was reported in this paper. To achieve optimized electro‐optical performance, deep‐UV micro‐LEDs with different electrodes were fabricated and analyzed in sizes from 200 × 200 to 10 × 10 μm 2 . At the same forward bias, the devices with Ti/Al‐based electrodes achieved 10 times injection current and three times electroluminescence intensity than those with Cr/Al‐based electrodes. The blueshift phenomenon of deep‐UV light was observed from 292 nm at 2 A/cm 2 to 287 nm at 200 A/cm 2 with the increasing current density. By the excitation of deep‐UV micro‐LED, quantum dot film achieved high light conversion efficiency and optimized color rendering, as the converted color emission peak was separate from the pumping source. The high energy of deep‐UV photons and the narrow emission bandwidth of QDs resulted in prominent color purity. The forward voltage and electroluminescence intensity uniformity of a 250 × 250 micro‐LED array with each pixel size of 30 × 30 μm 2 were further discussed. The optical microscope images of green QD film pumped by a deep‐UV micro‐LED demonstrated its competitive application in the color‐converted display. Abstract : The QD‐converted light emission peak was separated from the deep‐UV excitation source, optimizing the color rendering. Prominent light conversion efficiency and color purity were achieved due to the high energy of deep‐UV photons and narrow emission bandwidth of QDs.